Chuyển vị H tới N, O và S qua trạng thái chuyển tiếp vòng 4 hoặc 5 cạnh trong phản ứng phân mảnh ở phổ EI MS - Đĩnh, Nguyễn Hữu; Tuyết Lan, Hoàng Thị; Hoan, Phạm Văn (Vietnam Journal of Chemistry, 2014)
EI MS of several of series of organic compounds were interpreted. It is demonstrated that: for compounds containing  >N-N=CH-  group, the fragmentation reaction is characterized by a rearrangement with a migration of H to N via four-membered ring transition state ; for compounds containing  -O-CH2-COOH , -O-CH2-CONH- or -S-CH2-COOH  group, a rearrangement of H to O, N or S via five-membered ring transition state happened.